(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
The article analyzes the role of emotions and volitional processes in human psychological thinking, as well as the mechanisms for their regulation in conflict situations. Emotions shape a person’s mental state, as well as motivate activity and play an important role in the process of achieving a goal. Voluntary processes guide a person toward making correct decisions and managing emotions in complex and uncertain situations. The article provides a psychological characterization of emotional states such as affect, frustration, aggressiveness, and depression, and reveals strategies for volitional regulation during conflicts. The research results offer practical recommendations for strengthening emotions and willpower, as well as for optimal management in conflict situations. This article, combining modern theories and the practice of psychology science, focuses on ensuring personal development and societal stability